Hubungan antara Pesan Persuasif dengan Sikap Followers di Media Sosial - Refika Noorkesuma Mukti; Firmansyah (Bandung Conference Series: Journalism, 2022)
Abstract. The process of delivering messages in this digital era continues to grow and becomes easier, of course the development of the internet affects it. The media that is the main stream of message delivery today is social media, and one of them is Instagram. Instagram is not only used by individuals but also organizations that have an impact on society. Including Greenpeace Id as a non-governmental environmental organization who spreads information about the environment on their Instagram. The spread of messages carried out by Greenpeace is persuasive which aims to provide awareness to their Instagram followers. In accordance with the identification of the problem, this study aims to see how the relationship of persuasive messages on Instagram @greenpeace.id through aspects of the central route and peripheral route with the attitude of their followers. This research uses correlational study method. Data collection techniques were carried out by distributing questionnaires, literature studies and online data searches. To dissect this research, cognitive psychology theory, S-O-R theory, elaboration possibility theory and attitude theory are used. The sampling technique used is purposive sampling with several criteria that the authors have determined. For sampling author using slovin and obtained as many as 100 respondents. In testing the validity and reliability of questions distributed questionnaires can be said to be valid and reliable. The results in this study have a significant relationship between persuasive messages on Instagram @greenpeace.id and the attitude of taking care the environment of their followers. Abstrak. Proses penyampaian pesan di era digital ini terus berkembang dan menjadi semakin mudah tentu saja perkembang internet mempengaruhi hal itu. Media yang menjadi arus utama penyampaian pesan saat ini adalah media sosial salah satu platformnya yaitu Instagram. Instagram tidak hanya digunakan oleh individu tetapi juga organisasi yang mempunyai pengaruh untuk masyarakat. Termasuk Greenpeace Id sebagai organisasi lingkungan non Pemerintah yang menyebarkan infromasi mengenai lingkungan hidup dari platform Instagramnya. Penyebaran pesan yang dialkukan oleh greenpeace bersifat persuasif yang memang bertujuan untuk memberikan awareness kepada para pengikut Instagramnya. Sesuai dengan identifikasi masalah, penelitian ini bertujuan untuk melihat bagaimana hubungan pesan persuasif dalam Instagram @greenpeace.id melalui aspek central route dan peripheral route dengan sikap para followersnya. Penelitian ini menggunakan metode studi korelasional. Teknik pengumpulan data dilakukan dengan cara menyebarkan kuesioner, studi pustaka dan penelusuran data online. Untuk membedah penelitian ini digunakan teori psikologi kognitif, teori S-O-R, teori elaborasi likelihood dan teori sikap. Teknik sampling yang digunakan adalah purposive sampling dengan beberapa kriteria yang telah penulis tentukan. Pengambilan sampel menggunakan slovin dan didapatkan sebanyak 100 responden. Pada uji validitas dan reliabilitas pertanyaan untuk penyebaran angket dapat dikatakan valid dan reliabel. Hasil dalam penelitian ini adanya hubungan yang signifikan hubungan antara pesan persuasif dalam Instagram @greenpeace.id dengan sikap menjaga lingkungan followersnya.